Kosovo : A Future of Green Transport and Clean Air - World Bank Group (World Bank, Washington, DC, 2019)
The Western Balkans is home to the most polluting power plants in Europe, and its transport and energy infrastructure require updates. Not surprisingly, countries such as Kosovo, are suffering from severe urban air pollution and traffic congestion as a result of high dependence on fossil fuels in the energy matrix, inefficient transport system and aging vehicle fleets. These substantially harm public health, productivity and efficiency in urban mobility. Kosovo is implementing the EU enacted Stabilization Tracking Mechanism programme, aiming to gradually integrate its national policies on legal, economic and social matters with the EU. On 6 February 2018, the European Commission published its expansion plan to cover up to six Western Balkan countries including Kosovo with potential accession as members of the EU after 2025. This is relevant for vehicle emissions as it entails implementation of EU vehicle emission and fuel standards. The development objective of this project is to support the government of Kosovo and City of Pristina to develop strategies to reduce emissions and pollutions from transport perspective, such as modernization and better management of public and private vehicle fleets, and to scope for components and activities to be considered as part of potential Develop Policy Financing or Investment Project Financing by the World Bank The layout of the report includes the following sections: Chapter second realizes a rapid assessment of vehicle pollution for Kosovo including vehicle emission trends. Chapter third list in a summarized manner major instruments to reduce transportation emissions. Based on the problem and solution description policies are selected which are assessed in further detail to curb vehicle emissions in Kosovo. These policies or interventions were selected based on on-going plans and activities and interest from the Government. They include usage of low-emission buses (chapter fourth), fiscal instruments to promote low-emitting vehicles (chapter fifth) and implementation of in-service vehicle emission testing.